Effects of Nabilone on Sleep Outcomes in Patients with Parkinson's Disease: A Post‐hoc Analysis of NMS‐Nab Study. Issue 6 (31st May 2022) - Peball, Marina; Seppi, Klaus; Krismer, Florian; Knaus, Hans‐Günther; Spielberger, Sabine; Heim, Beatrice; Ellmerer, Philipp; Werkmann, Mario; Poewe, Werner; Djamshidian, Atbin
ABSTRACT: Background: The synthetic tetrahydrocannabinol analogue nabilone improved overall non‐motor symptom (NMS) burden in Parkinson's disease (PD) patients in comparison to placebo. Objectives: To characterize the effects of nabilone on different sleep outcomes in PD patients. Methods: We performed a post‐hoc analysis of the controlled, double‐blind, enriched enrollment randomized withdrawal NMS‐Nab study to assess the effects of nabilone on sleep outcomes in study participants who reported clinically‐relevant sleep problems (MDS‐UPDRS‐1.7 ≥ 2 points). Results: After open‐label nabilone administration, 77.4% reported no relevant sleep problem. In the withdrawal phase of the trial, the MDS‐UPDRS‐1.7. and the NMS‐Scale Domain 2 (i.e., Sleep/Fatigue) significantly worsened only in PD patients in the placebo group, which was mostly driven by a significant worsening of insomnia (question 5 of the NMS‐Scale Domain 2). Conclusions: This post‐hoc analysis of the NMS‐Nab trial suggests that nabilone has beneficial effects on sleep outcomes in PD patients experiencing sleep problems at baseline. The original trial was registered with ClinicalTrials.gov (NCT03769896, https://clinicaltrials.gov/ct2/show/NCT03769896 ) and EudraCT (2017–000192‐86).